A Framework of Project-Based Learning for Enhancing Student Competencies through Digital Video Production - Hoe, L.S.; Chuan, T.C.; Husin, H. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
This study research was aims to provide a framework, a set of guideline for secondary school pedagogical change. Thus, project-based learning(PBL) is a key to support students more competitive in an external environment. Students produce an educational video based on the topic they are learning. Integrating technology in PBL to enhance student competencies based on education curriculum Malaysia, which consist of communication, collaboration, creation, critical thinking. The data were collected through a questionnaire for 63 respondents. The results show significant positive results in terms of student competencies. PBL framework provides appropriate structure for determining all level of student competencies